Supply-side effects of strong energy price hikes in German industry and transportation - Thomas A. Knetsch; Alexander Molzahn (Deutsche Bundesbank, 2009)
The paper studies the short-term effects of energy price hikes on the supply of industrial goods and transport services including the repercussions on remuneration of input factors. While industry had suffered more strongly from the oil price shock of the late 1970s compared with the one of the early 1970s and the 2004-08 upsurge, evidence is reverse for transportation. Regarding the impact on the income distribution, both sectors share the pattern that in the recent episode rising energy costs were more than compensated by falling unit labor costs while in the 1970s cost structures had been strained by expansive wage policy in addition to the oil price shocks.
Keywords: E23; E25; Q43; 330; Energy prices; supply of goods and services; income distribution; Mineralölpreisschock; Verarbeitendes Gewerbe; Verkehrsgewerbe; Angebot; Verteilungswirkung; Deutschland